Effect on Soil Properties of BcWRKY1 Transgenic Maize with Enhanced Salinity Tolerance. (20th November 2016) - Zeng, Xing; Zhou, Yu; Zhu, Zhongjia; Zu, Hongyue; Wang, Shumin; Di, Hong; Wang, Zhenhua
Abstract : Maize ( Zea mays L.) is the most important cereal crop in the world. However, soil salinity has become a major problem affecting plant productivity due to arable field degradation. Thus, transgenic maize transformed with a salinity tolerance gene has been developed to further evaluate its salt tolerance and effects on agronomic traits. It is necessary to analyze the potential environmental risk of transgenic maize before further commercialization. Enzyme activities, physicochemical properties, and microbial populations were evaluated in saline and nonsaline rhizosphere soils from a transgenic maize line (WL-73) overexpressing BcWRKY1 and from wild-type (WT) maize LH1037. Measurements were taken at four growth stages (V3, V9, R1, and R6) and repeated in three consecutive years (2012–2014). There was no change in the rhizosphere soils of either WL-73 or WT plants in the four soil enzyme activities, seven soil physicochemical properties, and the populations of three soil organisms. The results of this study suggested that salinity tolerant transgenic maize had no adverse impact on soil properties in soil rhizosphere during three consecutive years at two different locations and provided a theoretical basis for environmental impact monitoring of salinity tolerant transgenic maize.